Virtual Teaming: Leveraging Team Science Sense-Making During COVID-19. (23rd February 2021) - Portman, Diane G; Thirlwell, Sarah; Donovan, Kristine A; Ellington, Lee
Individuals with cancer anorexia cachexia syndrome (CACS) experience multifaceted distress. To address CACS patient concerns regarding their experience of care, our cancer center established a specialized CACS clinic in 2016. We applied the team science principle of the team mental model (TMM) to support development of an effective interprofessional collaborative CACS care team. In 2020, cessation of CACS clinic in-person visits during coronavirus disease 2019 (COVID-19) threatened the viability of the entrenched TMM and once again jeopardized the patient experience of care. We present a case-based vignette as a representative composite of patient experiences to illustrate the challenges. A 48-year-old female was referred to our CACS clinic for pancreatic cancer-associated appetite and weight loss during COVID-19. To reduce risk of infection, in-person clinic visits were curtailed. When informed about the resulting need to defer the CACS assessment, the patient and her spouse expressed concern that postponement would adversely affect her ability to undergo anticancer treatments or achieve beneficial outcomes. To minimize delays in CACS treatment and optimize the patient experience of care, we applied the team science principle of sense-making to help the team rapidly reformulate the TMM to provide interprofessional collaborative CACS care via telemedicine. The sense-making initiative highlights opportunities to examine sense-making within health care teams more broadly during and after the pandemic. The application of sense-making within interprofessional cancer care teams has not been described previously.